Spike(s) protein gene microevolution of SARS CoV-2 virus in Bolivian Population: correlation between phylogeny and contagion waves - NINAHUANCA TERÁN, ANELIZ; Tola, Emma Torres; Voigt, Daniela Andrea Arteaga; Barrón, Ruddy Luna (Journal of Health & Biological Sciences, 2024)
Objective: analyze the population gene structure and phylogeny of the S gene of the SARS CoV-2 virus of COVID-19 (+) patients from the Plurinational State of Bolivia and then correlate its phylogeny with the different waves of contagion. Methods: three SARS-CoV-2 samples obtained by nasopharyngeal swabs from positive COVID-19 patients were sequenced by Sanger sequencing. 488 sequences of Bolivian SARS-CoV-2 were downloaded from GISAID until September 25, 2023. The genetic structure and phylogeny were analyzed to correlate the presence of the different variants with the waves of contagion. Results: three (3) sequences of 623pb, 1557pb, and 3060pb of the S gene were obtained, and the last one was analyzed with the sequences downloaded from GISAID, obtaining a phylogenetic tree and a network of haplogroups that revealed the formation of clades and nodes that gave rise to variants of the six waves that Bolivian inhabitants faced. The Y508S mutation was identified as new since it was not identified in the CoVariants® and CoV-Glue® databases. Conclusions: the phylogeny, haplogroup network, and Person's correlation coefficient revealed the existence of a positive correlation between the microevolution of the analyzed fragment and the appearance of the different waves of contagion.